Optimization of Surface Roughness in CNC Turning of SS 304 Stainless Steel Using Respon Surface Methodology - Aiwa, Toto; Husman; Zaldy Kurniawan (Jurnal Rekayasa Mesin, 2025)
Surface roughness is one of the important indicators in assessing machining results, especially in stainless steel (SS 304). This study aims to determine the influence of machining parameters, namely spindle speed, feeding speed, and feeding depth on the surface roughness of stainless steel material (SS 304) in the turning process using the mori seiki sl-25 CNC machine. The research was conducted using the Response Surface Methodology (RSM) method and the experimental design of Box-Behnken Design (BBD) to obtain the best combination of parameters. Previous research has only examined two variables separately without considering the feed rate at the same time. The results of this study show that among the 3 factor variables, only one factor, namely the speed of interpretation that can reject Ho with a value of f calculated as 4.79>4.77, which means that the speed of interpretation has a significant influence on the degree of roughness compared to other variables.